2012
DOI: 10.1073/pnas.1203140109
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor receptor-dependent effects of repeated stress on tau phosphorylation, solubility, and aggregation

Abstract: Exposure and/or sensitivity to stress have been implicated as conferring risk for development of Alzheimer's disease (AD). Although the basis for such a link remains unclear, we previously reported differential involvement of corticotropin-releasing factor receptor (CRFR) 1 and 2 in acute stress-induced tau phosphorylation (tau-P) and solubility in the hippocampus. Here we examined the role of CRFRs in tau-P induced by repeated stress and the structural manifestations of altered tau solubility. Robust tau-P re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 56 publications
7
91
1
Order By: Relevance
“…Indeed, previous studies have shown that Tau hyperphosphorylation and neuronal/ synaptic atrophy is also triggered by different intrinsic and extrinsic conditions such as acute stress (45), hypothermia (46), hypometabolism (47), and hibernation (48) in a reversible way. However, repeated/prolonged exposure to stress is known to result in sustained Tau hyperphosphorylation as well as insoluble neurodamaging Tau aggregates (11,49,50); additionally, reversibility of stress-induced neuronal atrophy is lost in the aged brain (51). Thus, future studies are necessary to clarify the mechanistic role of Tau in the stress-recovery process as well as to identify the potential threshold/"point of no return" between Tau-related neuroplasticity and neuropathology under stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown that Tau hyperphosphorylation and neuronal/ synaptic atrophy is also triggered by different intrinsic and extrinsic conditions such as acute stress (45), hypothermia (46), hypometabolism (47), and hibernation (48) in a reversible way. However, repeated/prolonged exposure to stress is known to result in sustained Tau hyperphosphorylation as well as insoluble neurodamaging Tau aggregates (11,49,50); additionally, reversibility of stress-induced neuronal atrophy is lost in the aged brain (51). Thus, future studies are necessary to clarify the mechanistic role of Tau in the stress-recovery process as well as to identify the potential threshold/"point of no return" between Tau-related neuroplasticity and neuropathology under stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mifepristone (Sigma) and antalarmin (Sigma) were dissolved in DMSO and diluted into 0.9% saline (20% DMSO) immediately before injection (20mg/kg). Dose and route of drug administration was based on previous studies (Furukawa-Hibi et al, 2012;Llorens-Martín and Trejo, 2011;Rissman et al, 2012;Webster et al, 1996). Vehicle injections were either 0.9% saline containing 5% EtOH, or saline containing 20% DMSO.…”
Section: Drugsmentioning
confidence: 99%
“…This has further downstream effects such as increasing levels of the neuroprotective sAPPα fragment, which reduces Aβ secretion and suggests a protective role for O-GlcNAc (Kim et al 2012). Finally, treatment with the O-GlcNAcase inhibitor NButGT in a mouse model of AD resulted in reduced γ-secretase activity and subsequent attenuation of Aβ plaque production and inflammation in vivo, further highlighting the important protective role of O-GlcNAc under conditions of stress and neurodegeneration (Rissman et al 2007(Rissman et al , 2012.…”
Section: Alzheimer's Diseasementioning
confidence: 99%